EVALUATION OF ACADEMIC QUALITY ACCORDING TO THE STUDENTS OF A PRIVATE UNIVERSITY OF HUANCAYO IN PERU - Bollet Ramírez, Frank (2019)
The Huancayo Franklin Roosevelt PrivateUniversity needs to monitor a set of educationalvariables as part of the institutional licensing processof the organization, among them, the educationalquality is the most outstanding, due to its importancein terms of achieving the mission and vision of theUniversity. Academic quality was divided into fivedimensions: study program planning, teachingmethodology, teacher management, certification,research, technological development and innovation.The objective of the research was to determinethe level of educational quality according to thestudents of the last cycle of the university in orderto recommend improvement mechanisms. Thestudy was quantitative, basic type, descriptivelevel, descriptive method and simple descriptivedesign. A census composed of 140 students ofthe tenth semester of the five professional schoolswas assumed. It was determined that the academicquality of the Huancayo Franklin Roosevelt PrivateUniversity, based on the perceptions of the tenthcycle students, reaches a good level with a 71%approval